Communicative competence: an analysis of the occurrence of politeness strategies and repetitions in L2 oral interactions / Dr Suryani Awang, Wan Nuur Fazliza Wan Zakaria and Siti Shazlin Razak - Awang, Suryani; Wan Zakaria, Wan Nuur Fazliza; Razak, Siti Shazlin (2018)
Social skills have long been recognized as important component that make up speakers’ communicative competence. One major component of social skills is soft skills which have received great recognition with the recent adoption of the concept Integrated Cumulative Grade Point Average (iCGPA) to measure Malaysian university students’ performance. Based on this concept, both students’ academic results and soft skills which include leadership, communication, entrepreneurial, social and critical thinking skills are taken into consideration in the grading system. Driven by this move, the current study aims to investigate the aspect of social skills among UiTM students in their oral interactions, particularly by examining their communicative competency during oral assessments in classrooms. To achieve this aim, some role play activities conducted by UiTM students taking ELC121 (Integrated Language Skills I) in UiTM Kelantan branch will be observed and recorded before the oral data are transcribed and analyzed. As the students are given only ten minutes to act out the role play (five minutes each for preparation and presentation), it is reasonable to assume that their interactions are spontaneous, hence, reflecting their real communicative competence in using the English language. The main focus of data analysis is on politeness strategies and repetitions because these components are expected to emerge significantly in most social interactions. The findings of this study help to provide greater understanding of participants’ L2 competency and soft skills and they also make valuable input for curriculum designers to gauge the appropriate competency level in language assessments in order to equip the students with greater social skills, hence, making them more competent in speaking English.